Role of Small Scale Enterprises Providing Immediate Large Scale Employment, and Offer More Equitable Distribution of the National Income: Impact of Small Scale Enterprises on Employment and Income Distribution (Journal of Advances and Scholarly Researches in Allied Education, 2012)
To achieve the objectives of the study, secondary as well as primarysources of data have been used. The major sources of secondary data include theofficial records of Haryana Financial Corporation (HFC) and Haryana StateIndustrial Development Corporation (HSIDC), Chandigarh and Panchkula. HFC andHSIDC emphasize the borrowers to submit their annual accounts regularly so asto monitor the repayments of their loans. To start with the financial statementsof as many as 100 small scale firms were collected from HFC and HSIDC. However,only 37 firms were kept in the final sample because of incompleteness of thedata or mismatch of the accounting period between various SSEs. To make thesample size large and more representative data on 28 SSIs was collected fromtheir books of accounts by visiting the offices of these firms.  In total, financial statements of 65 unitswere collected and analysed. Annual Economic Surveys of Government of India,Government of Haryana, relevant RBI publications, research journals like“Economic and Political Weekly”, SEDME, books and some Internet search engineslike Google have also been used for this purpose.